Treatment of supra condylar fractures of humerus in children, a SKIMS medical college study - Bhat, Jawed Ahmed; Wani, Arshad H.; Din, Abid; Dar, Reyaz; Mir, Naseer Ah (International Journal of Research in Orthopaedics, 2020)
Background: Supracondylar fractures of the humerus account for sixty percent of all fractures around the elbow in children. Delayed presentation of these fractures is very common even in developed countries. The aim of the present study was to evaluate the clinical, radiological and functional results following closed reduction (C/R) and percutaneous pinning of widely displaced supracondylar fractures of humerus. An objective of this study was to study supracondylar fractures of humerus in children in Skims medical College. Methods: A total 86 patients with displaced extension type supracondylar fractures (gartland type III) of humerus were managed by closed reduction and percutaneous fixation at Skims medical college after achieving optimal and satisfactory reduction. There were 52 boys and 28 girls. Average age was 6.69 years (range 2-12). Results: A total 86 patients were successfully treated with C/R and cross pinning. 6 patients were lost to follow-up. 80 patients with a minimum follow-up period of 12 months formed the basis of this study. Conclusions: C/R and pinning is effective method despite delayed presentation. Strict anatomical reduction and stable fixation minimises the risk of developing cubitus varus deformity.